Active surveillance of adverse drug events in hospitalized patients with pulmonary arterial hypertension based on the global trigger tool - Xu, Mengdan; Xiong, Shunyu; Chen, Guanquan; Li, Guozhi; He, Suzhen (Frontiers in Pharmacology, 2025)
ObjectiveTo explore the method of active monitoring of adverse drug events (ADEs) in patients with a rare disease: pulmonary arterial hypertension (PAH).MethodsFirst, initial trigger items were extracted and organized through literature-based evidence and drug inserts. Then, the trigger items were refined using expert consultation based on a Delphi method. Second, patients with PAH admitted to a hospital between 1 January 2022 and 1 June 2023 were extracted as study samples. A retrospective case review was conducted to verify the clinical applicability of triggers. We calculated indicators such as sensitivity, specificity, and positive predictive value (PPV), and also observed the ADEs. Risk factors for the development of ADEs in hospitalized patients with PAH were also analyzed.ResultsWe extracted and organized 31 initial trigger items. After two rounds of modification through expert consultation, 24 triggers were identified. We converted the trigger items into risk signals to automatically identify cases with possible ADEs with the help of the Chinese Hospital Pharmacovigilance System (CHPS). Manual review of suspected cases revealed that the overall PPV of the triggers was 30.30%, the sensitivity was 98.21%, and the specificity was 72.57%. The prevalence of ADEs detection was 17.57%, which was equivalent to 25.75 ADEs occurrences in 1,000 patient days and 11.84 ADEs occurrences in 1,000 medications. ADEs-involved organs included the blood system, and there was also damage to the gastrointestinal system, hepatic system, and renal system. ADEs severity was categorized into 24 grade D cases, 102 grade E cases, 15 grade F cases, and two grade H cases. The longer the duration of hospitalization, the higher the number of comorbidities, the higher the number of positive triggers, and the higher the likelihood of ADEs.ConclusionThis study provides a new method for actively identifying ADEs in hospitalized patients with PAH, as well as a reference for research on pharmacovigilance for rare diseases.